Synthesis of agronomic assessment for co-designed trials and recommendations - Monserrate, Fredy; Berre, David; Triomphe, Bernard; Baudron, Frédéric (2024)
This document presents a consolidated cross-country analyses of agroecological innovations and trials based on the agronomic assessments developed in each country participating in the CGIAR Agroecology Initiative (AEI). The document consolidates two key outputs of the consultancy GH-2024-0573: a comprehensive draft report on the assessment of co-designed trials and results across the eight countries, providing a critical analysis of similarities, differences, and challenges, along with recommendations for the next phase of the AEI initiative; and refined suggestions for inclusion in two WP1 products — the co-design guidelines and the cross-analysis report. The present document is based on the information contained in the compilation of agronomic assessment reports from the different countries.